The treatment of primary arthritis of the finger and thumb joint - Spies, Christian; Langer, Martin Franz; Hahn, Peter; Müller, Lars Peter; Unglaub, Frank (Deutsches Ärzteblatt, 2018)
Background: Primary finger and thumb joint arthritis is common, with a markedly rising prevalence from age 50 onward. As the population as a whole ages, the need for effective, stage-appropriate treatment of this condition is increasing. Methods: This review is based on pertinent publications retrieved by a selective search in the PubMed and Cochrane Library databases. Results: Pain on movement and morning stiffness are commonly reported symptoms. Thorough physical examination and plain x-rays are mandatory. In the early stages of primary finger and thumb joint arthritis, a conservative, multimodal treatment approach involving the use of splints, physiotherapy, and non-steroidal anti-inflammatory drugs can be helpful. The intraarticular injection of hyaluronic acid or cortisone seems to relieve pain in the short term, but its long-term efficacy in primary finger and thumb joint arthritis is questionable. Arthrodesis (joint fusion) is a reliable surgical treatment option for arthritis of the metacarpophalangeal and interphalangeal joints of the thumb. For mobility-preserving surgery of the metacarpophalangeal joints of the second through fifth fingers, silicone implant arthroplasty remains the gold standard. Symptomatic, advanced arthritis of the distal interphalangeal joint is most effectively treated with arthrodesis. Conclusion: The efficacy of conservative treatment has been documented in high-quality clinical trials, while that of surgical treatment has not. The various surgical methods have yielded benefits in routine clinical use, but these remain to be assessed in randomized and controlled trials.
Gesehen am 02.04.2020